2014
DOI: 10.1038/eye.2014.139
|View full text |Cite
|
Sign up to set email alerts
|

The noninvasive retro-mode imaging of confocal scanning laser ophthalmoscopy in myopic maculopathy: a prospective observational study

Abstract: Purpose To investigate the morphological features of myopic maculopathy with a new and noninvasive retro-mode imaging (RMI) technique using a confocal scanning laser ophthalmoscope. Methods A total of 42 patients (69 eyes) with myopic maculopathy were included. RMI combined with fundus photography, fundus fluorescein angiography, and optical coherence tomography together were used to observe and evaluate the morphological features of disease. Results Four in 4 eyes (100%) with macular retinoschisis were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Amongst the five studies identified as being on-topic, two evaluated OCTA [ 25 , 28 ], two evaluated spectral domain (SD) OCT [ 24 , 27 ], and one conducted evaluations of OCTA and SD-OCT [ 26 ]. The three studies assessing test accuracy of OCTA reported complete data on a total of 95 participants (101 eyes) [ 25 , 26 , 28 ], whilst the three studies evaluating SD-OCT reported complete data on 130 participants (161 eyes) [ 24 , 26 , 27 ]. Mean (standard deviation) age was 55.90 (7.71) years in the OCTA studies and 53.91 (11.10) years in the SD-OCT studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst the five studies identified as being on-topic, two evaluated OCTA [ 25 , 28 ], two evaluated spectral domain (SD) OCT [ 24 , 27 ], and one conducted evaluations of OCTA and SD-OCT [ 26 ]. The three studies assessing test accuracy of OCTA reported complete data on a total of 95 participants (101 eyes) [ 25 , 26 , 28 ], whilst the three studies evaluating SD-OCT reported complete data on 130 participants (161 eyes) [ 24 , 26 , 27 ]. Mean (standard deviation) age was 55.90 (7.71) years in the OCTA studies and 53.91 (11.10) years in the SD-OCT studies.…”
Section: Resultsmentioning
confidence: 99%
“…Negative control group: Excluded patients with co-existing retinal conditions, or previous ocular treatments in the study eye. 36 eyes of 28 patients (23 female, 5 male) Included in analysis: 21 eyes of 17 patients (14 female, 3 male) Mean age 57.8 ± 14.5 years Negative control group: 32 eyes of 32 patients (27 female, 5 male) Mean age 56.2 ± 14.4 years, range 26–84 OCTA vs FA a : Sensitivity 19/21, specificity 30/32 Su et al 2014 [ 27 ] Prospective study of patients who presented to a macular service centre in China with high myopia (<−6D and AL > 26.5 mm) and myopic maculopathy. Excluded patients with other retinal or choroidal diseases, or dense cataracts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9.12). Applying retro-mode imaging, a characteristic fingerprint and firework pattern at the corresponding area of a macular retinoschisis have been detected in the region of a macula retinoschisis [44,45]. Shimada et al have classified myopic traction maculopathy according to its location and extent from S0 through S4: S0: no retinoschisis; S1: extrafoveal; S2: foveal; S3: both foveal and extrafoveal but not the entire macula; and S4: entire macula [46].…”
Section: Myopic Macular Retinoschisismentioning
confidence: 99%
“…This enables the formation of pseudo-3D images, through the creation of a shadow to one side of the abnormal feature that is being investigated, which eventually enhances the contrast of the lesion. Knowing the ability of infrared lasers to penetrate deeper retinal layers, retromode imaging with infrared laser-technology has been used to evaluate retinal pathological changes in several retinal and choroidal diseases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%